Case Report: Intermittent Chest Pain With Cough, Fever, and Pericardial Effusion Over the Course of 1 Year in an 11-Year-Old Girl - Chen, Jing; Qin, Lu; Tang, Lan-Fang (Frontiers in Pediatrics, 2022)
A 11-year-old girl with repeated chest pain, fever and cough for more than 13 months, as well as pleural effusion and large pericardial effusion. She was misdiagnosed of tuberculosis and received anti-tuberculosis drugs for half a year. Within the past year, she also underwent two more thoracotomy and thoracoscopic partial pericaidiectomy. The final diagnosis of pulmonary paragonimiasis was established due to eosinophilia, the patient’s living habits of always drinking stream water and the positive antibodies against Paragonimus. Antiparasitic praziquantel therapy was effective. Therefore, paragonimiasis should be considered as a possibility in the differential diagnosis of tuberculosis in children.